ANALISIS PERKEMBANGAN PENULISAN KREATIF: TREN DAN INOVASI MELALUI PEMETAAN BIBLIOMETRIK - Fahman Nur Faizi; Nurhayatin, Titin; Rifa'i, Irfan (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to map trends and innovations in creative writing over the past decade through a systematic literature review approach enriched with bibliometric analysis. Data were obtained from 41 international publications analyzed using the Publish or Perish and VOSviewer software, providing a comprehensive overview of publication patterns, dominant keywords, and researcher collaboration networks. The findings reveal a significant increase in the number of publications on digital-based creative writing from 2010 to 2025, with major themes including creative writing, creativity, digital storytelling, pedagogy, and the integration of artificial intelligence. Keyword analysis indicates the presence of diverse research clusters, although most remain fragmented and not fully interconnected, thus offering opportunities for further exploration of less addressed topics such as digital literary genres or assessment among peers. In addition, author mapping shows the dominance of several key figures, although cross-country collaboration is still relatively limited. These findings highlight a paradigm shift in creative writing from conventional models to digital and collaborative approaches supported by technology, as well as the importance of developing new pedagogical strategies relevant to 21st-century literacy needs. Therefore, this research makes a significant contribution to the development of creative writing studies in the global and digital era.